수직상승형 고소작업차의 개발을 위한 구조해석 - 이상식(Sang-Sik Lee); 김준태(Jun-Tae Kim); 박원엽(Won-Yeop Park) (한국정보전자통신기술학회 논문지, 2017)
This study was carried out for the production of aerial work machinery in high place in the orchard. In the case of orchards, there are many unpaved roads and sloping grounds to solve the problem of overturning or safety problems when working in a orchard. For more stable operation, an automatic leveling system was designed. During the structural analysis, the horizontal sensor was installed in addition to the standard that we wanted. Based on the INVENTOR, the structural analysis through 3D modeling showed that the maximum tilt of the worker was 116.49Mpa on the left and 118.26Mpa on the right. 본 연구는 과수원에서 높은 곳에서의 작업을 진행함에 있어 안정적인 고소작업 기계차의 제작을 위하여 진행하였다. 과수원의 경우 비포장도로 및 경사진 지면이 많아 고소작업 기계차가 과수원에서 작업함에 있어 전복이 되거나 안전성에 관하여 문제가 되고 있는 부분을 해결하기 위함이다. 보다 안정적인 작업을 위하여 Auto leveling system을 설계 하였고 구조해석을 하는 도중 우리가 원하는 기준에 부합하지 않아 수평센서를 추가적으로 설치하였다. INVENTOR를 바탕으로 3D 모델링을 통해 구조해석을 한 결과 작업자가 작업할 수 있는 최대 기울어짐 정도는 좌측 116.49Mpa, 우측 118.26Mpa로 나타났다.